2015
DOI: 10.1007/s10585-015-9749-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic gain of the PRL-3 gene may represent poor prognosis of primary colorectal cancer, and associate with liver metastasis

Abstract: PRL-3 genomic copy number is increased in colorectal cancer (CRC), and PRL-3 expression is closely associated with lymph node and liver metastasis of CRC. However, the clinical significance of PRL-3 genomic gain for CRC remains obscure. Here, PRL-3 genomic status in 109 primary CRC tumors and in 44 CRC tumors that had metastasized to the liver, was quantified using real time PCR. Association of PRL-3 genomic status with clinicopathological factors and prognosis was assessed in detail. PRL-3 genomic gain was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
6
1
Order By: Relevance
“…PRL-3 is a member of the protein tyrosine phosphatase family, the members of which play important roles in signalling pathways. We recently reported that PRL-3 genomic amplification and overexpression were confirmed in gastric cancer, oesophageal squamous cell cancer, and CRC (23)(24)(25)(26), and we revealed a relationship between these changes and cancer invasion and a poor prognosis. Especially in terms of CRC, PRL-3 genomic gains (defined larger as over two-fold) were significantly increased in liver metastases (26).…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations
“…PRL-3 is a member of the protein tyrosine phosphatase family, the members of which play important roles in signalling pathways. We recently reported that PRL-3 genomic amplification and overexpression were confirmed in gastric cancer, oesophageal squamous cell cancer, and CRC (23)(24)(25)(26), and we revealed a relationship between these changes and cancer invasion and a poor prognosis. Especially in terms of CRC, PRL-3 genomic gains (defined larger as over two-fold) were significantly increased in liver metastases (26).…”
Section: Introductionsupporting
confidence: 50%
“…The genomic gain statuses of c-myc and EGFR were then compared with the PRL-3 genomic gain status in the 35 previously reported primary CRC and corresponding liver metastases (Fig. 1C) (26). In the primary CRC tumours, genomic gains in PRL-3, c-myc, and EGFR were seen in 4 (11%), 4 (11%), and 13 (37%) cases, respectively.…”
Section: Genomic Gains In Prl-3 C-myc and Egfr In Primary Crcmentioning
confidence: 85%
See 2 more Smart Citations
“…Interestingly, this PTP was undetectable in normal colorectal epithelia, but was expressed at low levels in primary tumors, indicating a possible oncogenic role for this phosphatase during cancer progression. Since this pioneering study, many research groups have corroborated this finding in colorectal cancer not only for PRL-3 [67][68][69][70][71][72][73][74][75] but also for the other two PRLs [76]. In most of these studies, high expression of PRL-3 correlates with poor survival, indicating that this PTP is a promising biomarker not only for early stages of colorectal cancer but also for colon metastases.…”
Section: Prl Expression In Tumors and Metastases: Emerging Biomarker mentioning
confidence: 82%